Editorial: MMP28 and macrophage polarization: orchestrating the attack of the mac. Issue 1 (1st January 2014) - Gan, Ye; Herzog, Erica L.
Abstract : Discussion on MMP28ˈs unrecognized role in the regulation of macrophage polarization and tissue fibrotic responses.